Effects of Cation Exchange Capacity and Dissolved Organic Matter of Soil Amendments on Chemical Forms of Heavy Metals in Soils - SAKURAI, Shinji; HORINO, Haruhiko; NAKAGIRI, Takao; MATSUO, Naho; NAKAMURA, Kimihito (Nōgyō Nōson Kōgakkai ronbunshū, 2022)
Engineering and biological removal techniques of heavy metals in contaminated farmlands are sometimes unfeasible because of high cost and low efficiency on a large scale. Thus, the immobilization of metals in soils to prevent toxic metal uptake into crops using organic amendments has gained prominence. However, it is unclear which property of organic amendments influences heavy metal immobilization. We observed the chemical forms of Cu, Cd, and Pb through soil batch tests to elucidate the factors of immobilization using cow manure, poultry manure, and rice straw, including composting for 1 or 3 months (CM, PM, RS0, RS1, and RS3, respectively). The results from the experiments showed that CM had a high immobilization effect due to high cation exchange capacity and the mechanism of immobilization varies according to heavy metals. Furthermore, PM can promote the mobility of the three heavy metals, likely due to the heavy metal and dissolved organic matter complex. Based on the chemical forms, it is determined that composting promotes the immobilization effect of Cu in dune sand.